Strategi Pembentukan Brand Image Solo Technopark - Karomah, Insani Nur; Hindra Hastuti, Nurnawati; Maria Herawati, Dewi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
AbstractSolo Technopark is an integrated area based on science and technology as an innovation and vocational center that combines elements of science and technology development, market needs, industry and business to strengthen regional competitiveness. With great potential as a center for technology-based economic growth, the success of Solo Technopark is highly dependent on the perception of brand image in the eyes of the public, investors, and technology talents. In an effort to increase public understanding of Solo Technopark, on August 1, 2023, a Public Relations (PR) division was formed in response to the increasing interest and need for information about this area. Previously, communication and visits to Solo Technopark were held by each division, but with the formation of the Public Relations division, information management became more systematic. The public has a positive view of the quality of Solo Technopark graduates, who are considered to have advantages in the job market. This is reinforced by testimonials from alumni who have been successfully channeled into the industry, creating a good reputation among the community. The revitalization of Solo Technopark is an important strategic step to increase the competitiveness of the area by improving physical infrastructure and strengthening the identity and image of the area as a center for innovation and technology development. Therefore, a strategy to form the right brand image is needed to introduce Solo Technopark to the wider community. This research aims to find out how the strategy for the formation of Solo Technopark after the revitalization stage to form a new image. This type of research is a qualitative research with reference to the theory of factors that form brand image according to Coaker in 2021. The results of the study show that the strategy of forming the brand image of Solo Technopark is quite good and structured which can be seen from the aspects of quality, facilities, and services after the revitalization. Although the image of Solo Technopark has been considered good by visitors, there are several aspects that need to be improved, for example parking area facilities and the diversity of information on the website so that it is easy to understand, especially for people outside the city of Surakarta. Keywords: Strategy, Brand Image, Solo Technopark.